Entrepreneurship Education Management in Enhancing the Entrepreneurial Competence of Students at Pondok Pesantren Fathul Ulum - Shobirin, Mochammad Syafiuddin; Masrokan, Prim; Fuadi, Imam (Journal of Pesantren and Diniyah Studies, 2024)
The implications for the entrepreneurial competence of students at Pondok Pesantren Fathul Ulum can be identified through research encompassing the planning, implementation, and evaluation of entrepreneurship education. The research method employed is qualitative with a phenomenological approach, utilizing in-depth observation, interviews, and documentation for data collection. SWOT analysis is used as the analytical technique. The validity test employs source triangulation and technique triangulation methods. The research results indicate that the planning of entrepreneurship education at Pondok Pesantren Fathul Ulum is incorporated into an entrepreneurship learning curriculum consisting of theory- and practice-based learning plans. Entrepreneurship education is conducted using two methods: theory-based learning and practice-based learning. Entrepreneurship education achievement is evaluated through two direct methods (learning process) and post-learning. The evaluation of entrepreneurship education learning uses the CIPP (Context, Input, Process, and Product) evaluation model. The entrepreneurial competence of students at Pondok Pesantren Fathul Ulum is designed to develop social and corporate entrepreneurship competencies. The management of entrepreneurship education has implications for students' acquisition of knowledge, skills, and attitudes, aiming to equip them with the ability and competence to become initiators in entrepreneurship.